nalysis of the problems of adaptation of first-year students to learning environment in high school on the technical specialties (Pedagogy of Higher and Secondary Education, 2016)
Muraskovska V. P. Analysis of the problems of adaptation of first-year students to learning environment in high school on the technical specialties.The article discusses some aspects of adaptation of first-year students to the learning environment in higher education on the technical specialities. The major difficulties and factors (both positive and negative) that influence the adaptation process of first-year students were determined. Adaptation of students to the learning environment in higher education on the technical specialities is a multi-level process that involves an element of social and psychological adaptation and promotes intellectual and personal possibilities of students. It is necessary to apply new educational technologies that focus on self-development, self-fulfillment and students studying in technical specialties.The proper organization of independent work to expand and deepen knowledge is extremely important to the learning environment in higher education on the technical specialities. Training sessions at the university, including lectures, with respect to the process of learning have only constituent, indicative character. Students must acquire knowledge through active work with textbooks, additional literature, academic and other sources.During the adaptation process of freshmen to the learning environment in higher education on the technical specialities it is necessaey to take into account the difficulties which is associated with the requirements of the university and the lack of preparedness of first year students. As the students have a new social role, new conditions of life and their ideas about university received before are not dominant, they cosider universities as a training tools for future professional activity.Important levers of successful adaptation of freshmen are to eliminate the negative factors that affect this process. An active position, joint activity of students and teachers are necessary for successful adaptation. The students should find and choose means and ways to achieve particular educational objectives by themselves and the teachers should create conditions for this. To speed up the adaptation process the impact of all factors simultaneously must be taken into account. Qualitatively new (in general) living standards in higher education can positively affect the entire structure of the student’s personality and play a major role in his adaptation to the profession.
Keywords: adaptation; an adaptation period; research; training adaptations; freshman; problem; factors; difficulties